α-Galactosylceramide-activated Vα14 natural killer T cells mediate protection against murine malaria - Gonzalez-Aseguinolaza, Gloria (The National Academy of Sciences, 2000)
Natural killer T (NKT) cells are a unique population of lymphocytes that coexpress a semiinvariant T cell and natural killer cell receptors, which are particularly abundant in the liver. To investigate the possible effect of these cells on the development of the liver stages of malaria parasites, a glycolipid, α-galactosylceramide (α-GalCer), known to selectively activate Vα14 NKT cells in the context of CD1d molecules, was administered to sporozoite-inoculated mice. The administration of α-GalCer resulted in rapid, strong antimalaria activity, inhibiting the development of the intrahepatocytic stages of the rodent malaria parasites Plasmodium yoelii and Plasmodium berghei. The antimalaria activity mediated by α-GalCer is stage-specific, since the course of blood-stage-induced infection was not inhibited by administration of this glycolipid. Furthermore, it was determined that IFN-γ is essential for the antimalaria activity mediated by the glycolipid. Taken together, our results provide the clear evidence that NKT cells can mediate protection against an intracellular microbial infection.